2021
DOI: 10.1080/10408398.2020.1867056
|View full text |Cite
|
Sign up to set email alerts
|

Formation and mitigation of PAHs in barbecued meat – a review

Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) are chemicals, which can occur in barbecued or grilled foods, and particularly in meats. They originate from incomplete combustion of the heat source, pyrolysis of organic compounds, or fat-induced flame formation. This review therefore summarizes relevant parameters for mitigation of especially carcinogenic PAHs in barbecued meat. Consumption of PAHs increases the risk of cancer, and thus the relevance for the mitigation of PAHs formation is very high for barbecued meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…In response to the hazard of carcinogens to human health, changes in processing conditions and the application of antioxidant agents have been seen as effective measures to decrease the content of BaP in grilled meat products 11,12 . Excessive PAHs can be effectively prevented by changing the processing temperature and time 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In response to the hazard of carcinogens to human health, changes in processing conditions and the application of antioxidant agents have been seen as effective measures to decrease the content of BaP in grilled meat products 11,12 . Excessive PAHs can be effectively prevented by changing the processing temperature and time 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, thermal processes such as smoking, grilling, barbecue, frying, roasting can cause high levels of PAH formation in meat due to high temperature, pyrolysis and intense smoke generation [8]. Indeed, it has been reported that meat and meat products contain high concentrations of PAH and are important sources for PAH exposure through foodstuffs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Protection Agency have determined 16 of these compounds as priority contaminants, considering their mutagenic and carcinogenic properties [3,14]. Benzo[a]pyrene (BaP) is classified as a Group 1 carcinogen, while the majority of other high molecular weight PAHs are largely classified in Group 2A (probably carcinogenic to humans) or Group 2B (possibly carcinogenic to humans) [19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) describe a group of organic compounds containing two or more aromatic rings [6]. They can contaminate meat through direct pyrolysis of food nutrients and from its deposition via smoke produced from incomplete combustion of organic matter [4]; thus, meats that have been smoked or barbequed often have high concentrations of PAHs [7]. Although PAHs are present ubiquitously throughout the environment, the main source of exposure is through the diet [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although PAHs are present ubiquitously throughout the environment, the main source of exposure is through the diet [8]. Whilst self-preparation of foods and meats can help to minimise PAH formation [7], processed meats still compose approximately 20% of meat intake of the Australian diet [9]. Once ingested, PAHs are metabolised to form carcinogenic metabolites [10].…”
Section: Introductionmentioning
confidence: 99%